Post-Carotid Endarterectomy Hypertension. Part 1: Association with Pre-operative Clinical, Imaging, and Physiological Parameters. (November 2017) - Newman, J.E.; Bown, M.J.; Sayers, R.D.; Thompson, J.P.; Robinson, T.G.; Williams, B.; Panerai, R.; Lacy, P.; Naylor, A.R.
Abstract : Objective/Background: Post-endarterectomy hypertension (PEH) is a well recognised, but poorly understood, phenomenon after carotid endarterectomy (CEA) that is associated with post-operative intracranial haemorrhage, hyperperfusion syndrome, and cardiac complications. The aim of the current study was to identify pre-operative clinical, imaging, and physiological parameters associated with PEH. Methods: In total, 106 CEA patients undergoing CEA under general anaesthesia underwent pre-operative evaluation of 24 hour ambulatory arterial blood pressure (BP), baroreceptor sensitivity, cerebral autoregulation, and transcranial Doppler measurement of cerebral blood flow velocity (CBFv) and pulsatility index. Patients who met pre-existing criteria for treating PEH after CEA (systolic BP [SBP] > 170 mmHg without symptoms or SBP > 160 mmHg with headache/seizure/neurological deficit) were treated according to a previously established protocol. Results: In total, 40/106 patients (38%) required treatment for PEH at some stage following CEA (26 in theatre recovery [25%], 27 while on the vascular surgical ward [25%]), while seven (7%) had SBP surges > 200 mmHg back on the ward. Patients requiring treatment for PEH had a significantly higher pre-operative SBP (144 ± 11 mmHg vs. 135 ± 13 mmHg; p  < .001) and evidence of pre-existing impairment of baroreceptor sensitivity (3.4 ± 1.7 ms/mmHg vs. 5.3 ± 2.8 ms/mmHg; p  = .02). However, PEH was not associated with any other pre-operative clinical features, CBFv, or impaired cerebral haemodynamics. Paradoxically, autoregulation was better preserved in patients with PEH. All four cases of hyperperfusion associated symptoms were preceded by PEH. Length of hospital stay was significantly increased in patients with PEH ( p  < .001). Conclusion: In this study, where all patients underwent CEA under general anaesthesia, PEH was associated with poorly controlled pre-operative BP and impaired baroreceptor sensitivity, but not with other peripheral or central haemodynamic parameters, including impaired cerebral autoregulation.